SYSTEMIC MASTOCYTOSIS: MOLECULAR LANDSCAPE AND IMPLICATIONS FOR TREATMENT - Monaldi, Cecilia; Sara De Santis; Manuela Mancini; Samantha Bruno; Michele Cavo; Simona Soverini (Mediterranean Journal of Hematology and Infectious Diseases, 2021)
Over the past decade we have witnessed major advances in the molecular characterization of systemic mastocytosis (SM). This has provided important information for a better understanding of the pathogenesis of the disease but has also practically impacted on the way we diagnose and manage it. Advances in molecular testing has indeed run in parallel with advances in therapeutic targeting of constitutive active KIT, the major driver of the disease. Assessing the molecular landscape in each individual SM patient is nowadays important for diagnosis, prognosis, treatment and monitoring of therapeutic efficacy. This is facilitated by the routine availability of novel technologies like digital PCR and NGS. This review aims to summarize the pathogenesis of the disease, discuss the value of molecular diagnostic testing and how it should be performed, and provide an overview of present and future therapeutic concepts based on fine molecular characterization of SM patients.